Principles of corporate finance. - Brealey, Richard A.; Myers, Stewart C.; Allen, Franklin, 1956-; Edmans, Alex (McGraw Hill series in finance, insurance, and real estate., 2025)
'Principles of Corporate Finance' bridges the gap between financial theory and practical application for corporate finance. It emphasises the importance of understanding financial theory to adapt to non-routine situations and evolving market conditions. By explaining why companies and financial markets behave as they do, the book equips managers with the tools to make informed decisions, not just based on experience but backed by theory. The authors address controversies within financial theory, offering balanced viewpoints while emphasising practical applications to increase company value.